Novel and emerging approaches to combat adolescent obesity - Manoj Sharma; Paul Branscum (Dove Medical Press, 2010)
Manoj Sharma, Paul BranscumHealth Promotion and Education and Public Health Sciences, University of Cincinnati, Cincinnati, OH, USAAbstract: Overweight and obesity continue to be health concerns facing today’s adolescent population. Along with metabolic and physical problems associated with obesity, today’s obese adolescents also face many psychological issues such as high rates of depression, anxiety, and social discrimination. Obesity is commonly recognized as having many causes, such as genetic, lifestyle and environmental. There are four major modalities for management of overweight and obesity in adolescents: dietary management, increasing physical activity, pharmacological therapy, and bariatric surgery. The purpose of this study was to conduct a review of novel and emerging approaches for preventing and managing adolescent obesity. It was found that while not always the case, theory driven approaches are being better utilized in newer interventions especially by those directed toward prevention. New theories that are being used are the theories of reasoned action, planned behavior, intervention mapping, and social marketing. Schools are found to be the most common place for such interventions, which is appropriate since virtually all children attend some form of private or public school. Limitations found in many studies include the underuse of process evaluations, the low number of studies attempted, environmental or policy changes, and that not all studies used a similar control group for comparison.Keywords: adolescent overweight, adolescent obesity, interventions